The role of antenatal education as a prevention of emerging disorders during pregnancy - Janicka-Kubiak, Elżbieta; Kubiak, Tomasz; Baranowska, Agata; Bulsa, Marek; Ciosek, Żaneta (Journal of Education, Health and Sport, 2022)
Introduction. The presented work is the result of a literature`s studies in the field of feeding pregnant women and experimental analysis on their knowledge and health behaviors. The study highlighted the importance of preventive actions by medical staff and school instructors in giving birth to the education of future mothers. The aim of the study was to determine the knowledge of pregnant women about the principles of proper nutrition. The analysis verified the ability to use the obtained data in the daily life of the respondents. Materials and method. The research group consisted of 101 pregnant women, including 51 patients from one of the Poznan`s Hospitals of Gynecological and Obstetrics Department and 50 participants of Birth School in the same city. The research tool was an authoritative questionnaire that included questions about the knowledge of pregnant women about the impact of a rational diet for a developing fetus. Results. On the basis of the data obtained it can be stated that students of childbirth schools were more willing and more likely to undertake pro-health activities than those who were never participants in such courses. The effectiveness of knowledge transfer by professionals is an important element of prevention of disorders during pregnancy. In educational programs, emphasis should be placed on the practical application of the acquired knowledge. Conclusions. The future mother should have clearly defined goals and principles in the rush of all the information. Thanks to them she will be able to consciously and without risk of complications as a result of bad eating habits, survive the period of nine consecutive months and enjoy the correct course of pregnancy and its completion.